2018
DOI: 10.1111/all.13666
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell chymase impairs bronchial epithelium integrity by degrading cell junction molecules of epithelial cells

Abstract: Background: An increased degree of mast cell (MC) degranulation and damage to the epithelial lining are prominent features of bronchial asthma. In asthmatic airways, it seems likely that epithelial cells will be exposed to increased concentrations of proteases from MC, though their actions on the epithelium are still not very clear. Methods: Bronchial rings from human lung tissue or 16HBE cell monolayer were incubated with MC chymase in different doses or various inhibitors. The sections of paraffin-embedded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Among epithelial cell-derived cytokines, IL-33 was the major cytokine rapidly released after Alternaria stimulation. Antigen inhalation also induces rapid release of endogenous chemical mediators such as proteases and tumor necrosis factor α by mast cells, which potentially damages epithelial cells in the lungs of antigen-sensitized individuals (22,23). In fact, after the third OVA aerosol challenge, although IL-33 levels in the lung homogenates were comparable between WT and Exph5-KO mice, rapid IL-33 release into the alveolar space was observed in Exph5-KO mice, but not in WT mice as mast cells where it regulates exocytosis (11,12), dendritic cells (DCs) (13), Th cells (7), and lung epithelial cells (14), all of which play essential roles in antigen-specific allergic immune responses in the lung, the roles of Rab27 in the net allergic immune responses in vivo are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among epithelial cell-derived cytokines, IL-33 was the major cytokine rapidly released after Alternaria stimulation. Antigen inhalation also induces rapid release of endogenous chemical mediators such as proteases and tumor necrosis factor α by mast cells, which potentially damages epithelial cells in the lungs of antigen-sensitized individuals (22,23). In fact, after the third OVA aerosol challenge, although IL-33 levels in the lung homogenates were comparable between WT and Exph5-KO mice, rapid IL-33 release into the alveolar space was observed in Exph5-KO mice, but not in WT mice as mast cells where it regulates exocytosis (11,12), dendritic cells (DCs) (13), Th cells (7), and lung epithelial cells (14), all of which play essential roles in antigen-specific allergic immune responses in the lung, the roles of Rab27 in the net allergic immune responses in vivo are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated whether epithelial barrier disturbance could also have a direct effect on MCs. Since an ongoing allergic inflammation directly contributes to an impaired epithelial barrier, an in vivo model of passive sensitization was developed to study the effects of barrier dysfunction on MC degranulation irrespective of inflammation. Mice were passively sensitized with r Der p 2‐specific murine IgE and subsequently exposed intranasally to chitosan (or sham) followed by r Der p 2 (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In a study using primary human bronchial epithelial cells, IL‐1β impaired the epithelial barrier . Another study using bronchial epithelial cells found that the MC mediator chymase plays an important role in impairing epithelial monolayers via the disruption of cell junctions . However, the direct contribution of a defective epithelial barrier to allergic sensitization and allergic inflammation remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where indicated, the migration was inhibited by addition of human chymase (C8118; Sigma-Aldrich) at a concentration of 10 munits per ml as described. 22…”
Section: Measurement Of the Outgrowth Rate From Limbal Explantsmentioning
confidence: 99%